Switchable Coumarins for Ratiometric pH Sensing - Mazza, Mercedes M. A.; Cardano, Francesca; Baker, James D.; Giordani, Silvia; Raymo, Françisco M. (Frontiers in Materials, 2021)
A fluorescent chromophore and a pH-sensitive heterocycle were integrated within a single covalent skeleton to generate four molecular switches with ratiometric fluorescence response. Upon acidification, the pH-sensitive heterocycle opens to shift bathochromically the absorption and emission bands of the fluorescent chromophore. As a result, an equilibrium between two species with resolved fluorescence is established with fast kinetics in aqueous environments. The relative amounts of the two interconverting forms and their relative emission intensities change with pH, providing the opportunity to probe this parameter ratiometrically with fluorescence measurements. Specifically, the resolved emissions of the two species can be collected in separate detection channels of the same microscope to map their ratio across a labeled sample and reconstruct its pH distribution ratiometrically with spatial resolution at the micrometer level. Additionally, the sensitivity of these molecular switches varies with the nature of the heterocyclic ring and with its substituents, allowing the possibility to regulate their response to a given pH range of interest with the aid of chemical synthesis. Thus, a family of valuable fluorescent probes for ratiometric pH sensing in a diversity of samples can emerge from the unique combination of structural and photophysical properties designed into our innovative molecular switches.